2008
DOI: 10.1002/lsm.20668
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism for visible light‐induced wound healing

Abstract: Visible light at high intensity can kill bacteria in infected wounds. Thus, illumination of infected wounds with intense visible light, prior to low intensity illumination for stimulating wound closure, may reduce infection and promote healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…However, neither wavelength was effective on the anaerobe P. acne. 14 More recently, Lipovsky et al 18 demonstrated that high-intensity broad-spectrum polychromatic light with wavelengths in the range of 400-1000 nm kills bacteria in infected diabetic ulcers.…”
Section: Introductionmentioning
confidence: 98%
“…However, neither wavelength was effective on the anaerobe P. acne. 14 More recently, Lipovsky et al 18 demonstrated that high-intensity broad-spectrum polychromatic light with wavelengths in the range of 400-1000 nm kills bacteria in infected diabetic ulcers.…”
Section: Introductionmentioning
confidence: 98%
“…In another study, Lipovsky et al [22] found that following illumination, colonies of Escherichia coli, Staphylococcus aureus and Staphylococcus marcescens were reduced by 62, 83 and 56% respectively. In our series, six patients with chronic sinuses (9-44 months), intractable to surgical and conservative measures, healed within 4 months (range: 1.5-4 months, mean: 2.17 months) of starting laser depilation.…”
Section: Discussionmentioning
confidence: 96%
“…Recently there were several publications on the bactericidal effect of visible light, most of them claiming that blue part of the spectrum (400 nm-500 nm) is responsible for killing various pathogens [1][2][3][4][5] . The phototoxic effect of blue light was suggested to be a result of light-induced reactive oxygen species (ROS) formation by endogenous bacterial photosensitizers which mostly absorb light in the blue region 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%